The accuracy of stereolithography medical model of sinonasal anatomical structures compare to 3D CT scan measurement - Din, Wan Shah Jihan Wan (2006)
Introduction Stereolithography is a relatively new tool in medicine. It has been used to produce many anatomical models in various fields. The accuracy of stereo lithography is thus essential to provide real replacement and time saving procedure. Objectives The objectives of this study are to develop stereolithography model for sinonasal region for ENT and craniofacial teaching and to assess the accuracy of stereo lithography model produced by our stereolithographic apparatus. It is also to evaluate the suitability of stereolithography model to be used as pre surgical planning for endoscopic sinus surgery together with an Image Guided System. If appropriate the model also will be used for surgical training for resident. Methodology Data with normal paranasal sinus was collected from USM craniofacial CT scan database. The images were processed with a specific procedure using MIMIC software. A stereolithography model was produced using the data. The model was compared with 3D CT scan image using specific landmark. The landmarks were divided into general craniofacial measurements and sinonasal measurements. The model was tried for simulated endoscopic sinus surgery using Image Guided System. Results The stereolithography model shows an accuracy of 99.82% for general craniofacial measurement and 99.68% for sinonasal measurement. Lamina papyracea thickness produces the largest error of28.71%. There is no pattern to indicate internal measurement group is opposite to the value of external measurement group. The stereolithography model is not suitable to be used as planning of endoscopic sinus surgery, since the anatomy requirement is very critical in the related area. Conclusion Stereolithography model is accurate in the dimensions that were measured. The model is suitable for planning in craniofacial surgery. However to be used as presurgical planning in endoscopic sinus surgery, it is still not detail enough. Further improvement in material used in stereolithography is needed before it can be utilised as presurgical model for endoscopic sinus surgery.